Identification of Criteria, Features and Levels of Economic and Managerial Competencies Development for Bachelors in Mechanical Engineering; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Lizunkov V. G. Vladislav Gennadyevich (2015, 2015)
Title screen